Silicon photonic resonator for label-free bio-sensing application - Suruk Udomsom (2018)
© 2018 SPIE. In medical diagnostics there is an increasing demand for biosensors that can specifically detect biological analytes in a fluid. Especially label-free sensing, consistings of a transducer with biorecognition molecules immobilized on its surface without relying on fluorescent dye. In this paper we study the design and fabrication of a silicon nanowire photonic ring resonator and its feasibility as a biosensor. We have simulated and fabricated racetrack ring resonators which have a few tenths of micrometer gap, up to 0.5 μm between the input / output waveguides and the resonators. It is found that the devices can be designed with large Q factors. Sensitivity to biomaterial detection has been simulated for antibody (goat anti-mouse IgG) - antigen (mouse IgG) using 3-dimensional Finite Difference Time Domain technique. The simulated results show that the ring resonator has a response 15 nm resonance shift per refractive index unit. Antibody coating method is also discussed in this paper which can be applied to other antibody-antigen types.